PENGARUH KOMPETENSI PROFESIONAL GURU AL-QUR’AN DAN LINGKUNGAN BELAJAR TERHADAP KUALITAS IBADAH PESERTA DIDIK DI SMK IT IBNU RUSYD BEKASI - Ferizal MS; Otong Surasman; Nurul Maulud Hudaini (Madani Institute : Jurnal Politik, Hukum, Ekonomi, Pendidikan dan Sosial-Budaya, 2021)
The research conducted by this writer aims to test and find out empirical data regarding the influence of professional competence of Al-Qur'an teachers and the learning environment on the quality of students' worship, either individually or simultaneously. In this study, the author used a quantitative method of correlation approach. The data collection technique used was the Multistage Random Sampling technique. The population in the research conducted by this writer was all students at SMK IT Ibnu Rusyd Bekasi which had 298 students. The sample in this study was 15% of the total population, namely 45 respondents. Data collection in this study was carried out using a questionnaire technique, observation and documentation. The type of analysis used is correlation and regression analysis which is described descriptively. The results of the research conducted by the author are: The First, there is a positive and insignificant influence between the professional competence of Al-Qur'an teachers on the quality of worship of students at SMK IT Ibnu Rusyd Bekasi. Furthermore, the correlation r = 0.025, it can be obtained that the coefficient of determination is R2 = 0.001 which means that it is 0.1%. The direction of influence is addressed by the regression equation: Ŷ Ŷ = 120,315-1,166 X1, it can be interpreted that every 1 point increase in the professional competence of the Al-Qur'an teacher (variable X1) will be followed by an increase in the quality of student worship (variable Y) of 119, 149 points . The Second, there is a positive and insignificant influence between the learning environment on the quality of student worship at SMK IT Ibnu Rusyd Bekasi. Furthermore, because the correlation coefficient r = 0.082, it can be obtained the coefficient of determination of R2 = 0.007 which means that 0.7% of the regression equation: Ŷ = 96.480 + 0.095X2, it means that every 1 point increase in the learning environment (variable X2) will be followed by an increase the quality of students' worship (variable Y) of 96.575 points. The Third, there is a positive and insignificant influence between the professional competence of al-Qur'an teachers and the learning environment on the quality of worship of students at SMK IT Ibnu Rusyd Bekasi. Furthermore, because the correlation coefficient r = 0.159. Then it can be obtained the coefficient of determination of R2 = 0.025, which means that 2.5%. The regression equation Y = 116,131 + (-0,155) X1 + 0.032 X2 means that every 1 point increase in the professional competence of the Al-Qur'an teacher (variable X1) and the learning environment (variable X2) together will be followed by the quality of the participants' worship. students (variable Y) of 116,008 points